Altered Biomechanical Properties of Gastrocnemius Tendons of Turkeys Infected with Turkey Arthritis Reovirus - Tamer A. Sharafeldin; Qingshan Chen; Sunil K. Mor; Sagar M. Goyal; Robert E. Porter (Veterinary Medicine International)
Turkey arthritis reovirus (TARV) causes lameness and tenosynovitis in commercial turkeys and is often associated with gastrocnemius tendon rupture by the marketing age. This study was undertaken to characterize the biomechanical properties of tendons from reovirus-infected turkeys. One-week-old turkey poults were orally inoculated with O’Neil strain of TARV and observed for up to 16 weeks of age. Lameness was first observed at 8 weeks of age, which continued at 12 and 16 weeks. At 4, 8, 12, and 16 weeks of age, samples were collected from legs. Left intertarsal joint with adjacent gastrocnemius tendon was collected and processed for histological examination. The right gastrocnemius tendon’s tensile strength and elasticity modulus were analyzed by stressing each tendon to the point of rupture. At 16 weeks of age, gastrocnemius tendons of TARV-infected turkeys showed significantly reduced (P<0.05) tensile strength and modulus of elasticity as compared to those of noninfected control turkeys. Gastrocnemius tendons revealed lymphocytic tendinitis/tenosynovitis beginning at 4 weeks of age, continuing through 8 and 12 weeks, and progressing to fibrosis from 12 to 16 weeks of age. We propose that tendon fibrosis is one of the key features contributing to reduction in tensile strength and elasticity of gastrocnemius tendons in TARV-infected turkeys.